Gamma-radiation spectra of 1200MeV electrons in thick beryllium, silicon and tungsten single crystals - Bochek, G.L.; Deiev, O.S.; Kulibaba, V.I.; Maslov, N.I.; Ovchinnik, V.D.; Potin, S.M.; Schramenko, B.I. (Вопросы атомной науки и техники, 2019)
Gamma radiation spectra of 1200MeV electrons from the single crystals of the beryllium 1.2mm thick, silicon 1.5mm and 15mm thick and tungsten 1.18mm thick along of the crystallographic axes were measured. Also spectral-angular distributions of gamma radiation from the silicon single crystals 1.5mm thick along of the crystallographic axes < 100 >, < 110 > and < 111 > were measured. On the basis of these measurements the γ-radiation spectra for the diﬀerent solid angles up to 6.97×10⁻⁶ sr were obtained.